1994
DOI: 10.1007/bf02052593
|View full text |Cite
|
Sign up to set email alerts
|

Is simple fistula-in-ano simple?

Abstract: All so-called simple fistulas-in-ano may not have readily detectable primary openings and may possess secondary tracks which preclude their behavior as simple fistulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
0
5

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 20 publications
3
73
0
5
Order By: Relevance
“…Since prior sonographic examinations had indicated that the fistulous remnant was present before the earlier surgery for perianal abscess, one might speculate that the 4 recurrences in our patient may have been associated with a previously unrecognized fistulous extension, inadequate prior surgical management, or perhaps premature wound closure. 3,8 This possibility is supported by the results of our microscopic examination of the tissue fragments removed at surgery, by the sonographic and surgical findings, and by the previous fistulographic findings, all of which were consistent with the location of a prior fistula site.…”
Section: Discussionmentioning
confidence: 53%
“…Since prior sonographic examinations had indicated that the fistulous remnant was present before the earlier surgery for perianal abscess, one might speculate that the 4 recurrences in our patient may have been associated with a previously unrecognized fistulous extension, inadequate prior surgical management, or perhaps premature wound closure. 3,8 This possibility is supported by the results of our microscopic examination of the tissue fragments removed at surgery, by the sonographic and surgical findings, and by the previous fistulographic findings, all of which were consistent with the location of a prior fistula site.…”
Section: Discussionmentioning
confidence: 53%
“…Approximately 32 to 52% of all recurrences occur in those cases in which an internal opening is not identified [12,14,15]. A failure to identify a secondary tract accounts for up to 38% of all recurrences [ 15,18]. Therefore, accurate assessment of the fistula is crucial to the success of fistula surgery and should include identification of the internal opening, course of the fistula, as well as the presence of any associated pathology (secondary tracts, abscesses).…”
Section: Discussionmentioning
confidence: 99%
“…Factors predictive of developing a postoperative recurrence foliowing fŸ surgery include the inability to locate the intemal opening and mismanagement of the fistula tract [15,18]. Approximately 32 to 52% of all recurrences occur in those cases in which an internal opening is not identified [12,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations